The use of elemental mass spectrometry in phosphoproteomic applications. Issue 3 (19th August 2014) - Maes, Evelyne; Tirez, Kristof; Baggerman, Geert; Valkenborg, Dirk; Schoofs, Liliane; Encinar, Jorge Ruiz; Mertens, Inge
Abstract : Reversible phosphorylation is one of the most important post‐translational modifications in mammalian cells. Because this molecular switch is an important mechanism that diversifies and regulates proteins in cellular processes, knowledge about the extent and quantity of phosphorylation is very important to understand the complex cellular interplay. Although phosphoproteomics strategies are applied worldwide, they mainly include only molecular mass spectrometry (like MALDI or ESI)‐based experiments. Although identification and relative quantification of phosphopeptides is straightforward with these techniques, absolute quantification is more complex and usually requires for specific isotopically phosphopeptide standards. However, the use of elemental mass spectrometry, and in particular inductively coupled plasma mass spectrometry (ICP‐MS), in phosphoproteomics‐based experiments, allow one to absolutely quantify phosphopeptides. Here, these phosphoproteomic applications with ICP‐MS as elemental detector are reviewed. Pioneering work and recent developments in the field are both described. Additionally, the advantage of the parallel use of molecular and elemental mass spectrometry is stressed. © 2014 Wiley Periodicals, Inc. Mass Spec Rev 35:350–360, 2016.